Sierra Leone : Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This paper discusses Sierra Leone's Request for a Three-Year Arrangement under the Poverty Reduction and Growth Facility (PRGF). Sierra Leone has made considerable progress during the last PRGF-supported program toward macroeconomic stability. Macroeconomic performance was generally strong, and structural reforms sought to establish a foundation for sound public finances and the effective conduct of macroeconomic policies. There were slippages in fiscal performance in 2005, but the government took corrective actions during the last quarter of the year to bring performance in line with the budget.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet